PROSPECTIVE LEGAL CONCEPT ON THE FULFILLMENT OF SUPPORT OBLIGATIONS FOR CONVICTED PERSONS - Wiyarso, Ardi; Yetti; Putra, Anggara (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
In many cases, prisoners serve as the primary breadwinners of their families, working to fulfill the needs of their wives and children before incarceration. When they begin serving their sentences, the families they leave behind often face severe economic hardship, which can lead to further social issues such as poverty, school dropouts, and even divorce. Although correctional institutions currently offer work training programs for inmates, these programs are generally not designed as productive work systems that guarantee fair wages or enable inmates to financially support their families. In cases where wages are provided, they are often symbolic or extremely minimal, with no systematic regulation within the national legal framework. Therefore, a legal breakthrough is needed in the form of regulation that affirms the rights of prisoners to work, receive fair compensation, and allocate their earnings to fulfill their family obligations. This study aims to analyze the concept of legal regulation concerning the obligation of prisoners to provide financial support, as well as to identify legal obstacles to the implementation of this obligation. The research method used is normative legal research. The findings indicate that the legal concept regarding the obligation of inmates to provide financial support remains largely unregulated under Indonesian law. Although prisoners retain responsibilities as heads of households, there is no binding legal mechanism requiring them to support their families during incarceration. While some correctional facilities offer work training and handicraft production programs, there is no structured system linking the income generated to the legal obligation of supporting their families. This highlights the urgent need for more operational, progressive, and socially just legal regulations. The legal perspective on the obligation of inmates to provide support holds that incarceration does not nullify this duty. Both marriage law and the Compilation of Islamic Law continue to require husbands or parents to provide financial support. However, there are currently no specific norms or provisions in Indonesian positive law that directly regulate or enforce this obligation in the context of incarceration. As a result, the families of inmates often lose their primary source of income without adequate legal protection. An ideal legal framework should align inmates’ rights as correctional residents with their social obligations as family heads, materialized through fair and responsive legal arrangements that reflect social realities.